2015
DOI: 10.1038/nutd.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabolic profiling in healthy individuals overfed different types of fat: links to changes in liver fat accumulation and lean tissue mass

Abstract: Background:Overeating different dietary fatty acids influence the amount of liver fat stored during weight gain, however, the mechanisms responsible are unclear. We aimed to identify non-lipid metabolites that may differentiate between saturated (SFA) and polyunsaturated fatty acid (PUFA) overfeeding using a non-targeted metabolomic approach. We also investigated the possible relationships between plasma metabolites and body fat accumulation.Methods:In a randomized study (LIPOGAIN study), n=39 healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Unsaturated fatty acids can be further divided by the number of double bounds as mono-(MUFAs; a single double bound) and poly-unsaturated fatty acids (PUFAs; more than one double bound) [163]. SFAs, MUFAs and PUFAs present different biological properties.…”
Section: Fatty Acids: Saturated Monounsaturated and Polyunsaturatedmentioning
confidence: 99%
See 2 more Smart Citations
“…Unsaturated fatty acids can be further divided by the number of double bounds as mono-(MUFAs; a single double bound) and poly-unsaturated fatty acids (PUFAs; more than one double bound) [163]. SFAs, MUFAs and PUFAs present different biological properties.…”
Section: Fatty Acids: Saturated Monounsaturated and Polyunsaturatedmentioning
confidence: 99%
“…Numerous beneficial healthy effects have been attributed to unsaturated fatty acids, including protection from obesity, diabetes, cancer, and atherosclerosis [162,164]. The most abundant MUFA in typical diets is oleic acid (C18:1n-9) which is effective in lowering the inflammatory response and LDL levels; that together contribute in the reduction of CVD risk [162,163]. High levels of MUFAs were described in the prevention of abdominal fat accumulation.…”
Section: Fatty Acids: Saturated Monounsaturated and Polyunsaturatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Focused on understanding the mechanism of such weight gain, a metabolomics study investigated the effect of overfeeding of saturated fatty acids (SFA) and polyunsaturated fatty acids (PUFA). 153 Here polar metabolites were evaluated for differentiation between SFA and PUFA diet-based body fat deposition. Finally, a metabolomics study focused on identifying dietary markers for coffee consumption identified 2-furoylglycine as a reliable marker.…”
Section: Applicationsmentioning
confidence: 99%
“…Atom-specific information generated by quantum mechanical calculations or by experimental data from NMR spectroscopy or X-ray diffraction needs to be associated with standard atom nomenclature. One well-known application of such atom specific data is in NMR metabolic profiling, a method widely used for enhancing our understanding of cellular mechanisms and for identifying metabolic biomarkers 38 , 39 , 40 , 41 , 42 , 43 , 44 . The process of quantifying a metabolite from an 1D- 1 H NMR spectrum requires that NMR peaks from the experiment be matched against those of a reference spectrum, for example from the Biological Magnetic Resonance Data Bank (BMRB 21 ) or the Human Metabolome Data Bank (HMDB 22 , 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%